2017
DOI: 10.1149/2.0161706jss
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Precursor Approach to Pristine Fullerene Film as Electron Selective Layer in Perovskite Solar Cells

Abstract: In perovskite solar cells (PSCs), electron selective layers (ESLs) assume a crucial role in blocking holes and transporting electrons for high performances. To achieve low-temperature solution processing of PSCs, organic n-type materials such as fullerene-based molecules have recently been employed to replace a typical TiO 2 ESL that requires high temperature (>450 • C) for fabrication. Herein, soluble C 60 -9-methylanthracene mono-adduct (C 60 (9MA)) is used as a thermal precursor to the C 60 ESL in planar PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…36,37 Different fullerene derivatives such as cis-a-dimethoxy carbonyl fulleropyrrolidine C 70 (DMEC 70 ), cross-linked silanemodified fullerene, and doped fullerene have been used as ESLs in p-i-n planar heterojunction structure 28,52,53 and later in the n-i-p architecture. 54 Umeyama et al 55 reported for the first time the use of C 60 thin films as the ESL in regular n-i-p PSCs, after thermal retro-Diels-Alder reaction on as-prepared glass/FTO/C 60 -9-methylanthracene. Fullerene ESLs have also been doped with various materials such as decamethylcobaltocene, 56 oleamide, 29 carbon, and novel two-dimensional carbon materials such as graphdiyne 57 for application in PSCs.…”
Section: Fullerenesmentioning
confidence: 99%
“…36,37 Different fullerene derivatives such as cis-a-dimethoxy carbonyl fulleropyrrolidine C 70 (DMEC 70 ), cross-linked silanemodified fullerene, and doped fullerene have been used as ESLs in p-i-n planar heterojunction structure 28,52,53 and later in the n-i-p architecture. 54 Umeyama et al 55 reported for the first time the use of C 60 thin films as the ESL in regular n-i-p PSCs, after thermal retro-Diels-Alder reaction on as-prepared glass/FTO/C 60 -9-methylanthracene. Fullerene ESLs have also been doped with various materials such as decamethylcobaltocene, 56 oleamide, 29 carbon, and novel two-dimensional carbon materials such as graphdiyne 57 for application in PSCs.…”
Section: Fullerenesmentioning
confidence: 99%
“…Compared to the PSCs without the He DBDjet treatment, the PSCs with the He DBDjet treatment exhibited smaller hysteresis, defined as (PCE (forward scan)-PCE (reverse scan))/PCE (forward scan), as shown in Figure S1 [4,52,53]. Many parameters influence the J-V hysteresis behavior of the PSCs, such as the voltage range, scan direction, scan rate, architecture, and precondition of PSCs [54][55][56][57][58][59][60][61][62][63]. In this case, without the He DBDjet treatment on the BCP layer, the unbalanced electron and hole transport rates as well as interface defects may cause photocurrent hysteresis [4,52,53].…”
Section: Statistical Analysis Of Pv Parametersmentioning
confidence: 99%